2021
DOI: 10.1007/s00586-021-07010-z
|View full text |Cite
|
Sign up to set email alerts
|

Jumper’s fracture of the sacrum: a novel and reproducible way for successful reduction and fixation

Abstract: Purpose Surgical treatment of jumper’s fractures is a highly demanding situation for the surgeon due to its rareness and frequent association with severe concomitant injuries. There is no current consensus regarding a standard treatment approach, thus reducing quality of care. Our objectives were to describe, apply and assess a novel surgical technic. Methods The presented research is an observational retrospective study of patients who underwent the descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…For displaced type 3 sacral fractures, Linhart et al [ 43 ] in 2022 presented a two-staged reduction method using maneuvers on hardware: vertical displacement was reduced by distracting L4 pedicle and iliac screws, and anterior displacement was corrected using rod persuasion into L5 pedicle screws ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For displaced type 3 sacral fractures, Linhart et al [ 43 ] in 2022 presented a two-staged reduction method using maneuvers on hardware: vertical displacement was reduced by distracting L4 pedicle and iliac screws, and anterior displacement was corrected using rod persuasion into L5 pedicle screws ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Type 2 and 3 U-shaped sacral fractures (equivalent AO Spine C3) frequently require surgical stabilization. Multiple efficient reduction techniques have been proposed, including external maneuvers [ 7 ], osteotomy [ 42 ], and hardware maneuvers [ 43 ]. Stabilization is achieved using triangular spinopelvic fixation, either with the technique by Schildhauer et al [ 11 ] or modified fixation using a transverse connector [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant biomechanical advantage of spinopelvic fixation is its ability to create a bridge between the intact lumbar vertebra and the intact iliac wings, restoring spinopelvic dissociation. A study by Linhard et al [ 18 ], involving 24 cases, reported achieving ideal anatomical reduction in all patients and did not encounter signs of screw loosening or implant insufficiency during follow-ups. Defects and fragmentation in the sacrum do not significantly impair the strength of fixation.…”
Section: Discussionmentioning
confidence: 99%